Association of Access to the Radial Artery with Reduced Incidence of Acute Kidney Injury: Association of Access to the Radial Artery - Gandhi, Sanjay; Khan, Haris; Bin Tariq, Umer; Ullah, Gulfan; Zubair, Akmal (Pakistan Journal of Health Sciences, 2023)
The research looks at access to the radial artery in contemporary medicine to lower the occurrence of acute kidney injury (AKI). In an effort to increase patient-centered procedural safety, it evaluates evidence contrasting radial versus femoral access. Objective: To determine if access to the radial artery and the prevalence of AKI during interventional procedures, with an emphasis on evaluating the possible advantages of radial access in lowering the risk of AKI. Methods: An examination of 132 instances classified by access location (radial artery as opposed to other sites) was done retrospectively. Beginning in September 2022 and ending in March 2023, the study’s length was six months. AKI incidence, procedure specifics, and demographic data were compared. The independent influence of radial access on the risk of AKI was evaluated using multivariate logistic regression. Results: The radial artery group (13.6%) exhibited a significantly lower AKI incidence than the comparator group (27.3%). Multivariate analysis confirmed the independent association. Conclusions: The possible relevance of access to the radial artery in reducing post-procedural AKI highlights the possibility of a safer alternative. Evidence-based access site selection is becoming more crucial in the age of patient-centered healthcare to improve procedural outcomes.